Tree diversity is key for promoting the diversity and abundance of forest‐associated taxa in Europe. Issue 2 (13th January 2020) - Ampoorter, Evy; Barbaro, Luc; Jactel, Hervé; Baeten, Lander; Boberg, Johanna; Carnol, Monique; Castagneyrol, Bastien; Charbonnier, Yohan; Dawud, Seid Muhie; Deconchat, Marc; Smedt, Pallieter De; Wandeler, Hans De; et al.
Abstract : Plant diversity is an important driver of diversity at other trophic levels, suggesting that cascading extinctions could reduce overall biodiversity. Most evidence for positive effects of plant diversity comes from grasslands. Despite the fact that forests are hotspots of biodiversity, the importance of tree diversity, in particular its relative importance compared to other management related factors, in affecting forest‐associated taxa is not well known. To address this, we used data from 183 plots, located in different forest types, from Mediterranean to Boreal, and established along a climatic gradient across six European countries (FunDivEUROPE project). We tested the influence of tree diversity, tree functional composition (i.e. functional trait values), forest structure, climate and soil on the diversity and abundance/activity of nine taxa (bats, birds, spiders, microorganisms, earthworms, ungulates, foliar fungal pathogens, defoliating insects and understorey plants) and on their overall diversity and abundance/activity (multidiversity, multiabundance/activity). Tree diversity was a key driver of taxon‐level and overall forest‐associated biodiversity, along with tree functional composition, forest structure, climate and soil. Both tree species richness and functional diversity (variation in functional trait values) were important. The effects of tree diversity on the abundance/activity of forest‐associated taxa were less consistent. Nonetheless, spiders, ungulates and foliar fungal pathogens were all more abundant/active in diverse forests. Tree functional composition and structure were also important drivers of abundance/activity: conifer stands had lower overall multidiversity (although the effect was driven by defoliating insects), while stands with potentially tall trees had lower overall multiabundance/activity. We found more synergies than tradeoffs between diversity and abundance/activity of different taxa, suggesting that forest management can promote high diversity across taxa. Our results clearly show the high value of mixed forest stands for multiple forest‐associated taxa and indicate that multiple dimensions of tree diversity (taxonomic and functional) are important.